Positional change of the condyle after orthodontic-orthognathic surgical treatment: is there a relationship to skeletal relapse? - Zafar, Husanov (The Korean Association of Oral and Maxillofacial Surgeons, 2014)
OBJECTIVES: The purpose of this study was to evaluate the condylar position in relation to the glenoid fossa before and after orthodontic-orthognathic surgical treatment and to investigate the relationship with skeletal relapse. MATERIALS AND METHODS: Lateral cephalograms and temporomandibular joint tomograms from 19 patients with mandibular prognathism who received orthodontic-orthognathic surgery were included in this study. Samples were divided into two groups based on skeletal change during the retention period. The relapse group consisted of 7 patients (3 females and 4 males; mean age, 21.9 years) whose pogonion or menton displaced more than 1 mm during the retention period and the stable group consisted of 12 patients (5 females and 7 males; mean age, 21.7 years). Anterior joint space, posterior joint space, superior joint space, and anteroposterior index were measured on tomograms at pretreatment and posttreatment timepoints. Condyle position and frequency of the positional change were compared between both groups. RESULTS: In the relapse group and stable group, 42.9% and 45.8% of the condyles, respectively, showed forward or backward displacement at posttreatment. However, the changes were small and the mean anterior, posterior, superior joint spaces and frequencies of the positional changes did not differ statistically between both groups. CONCLUSION: Our results suggest that small positional changes of the condyle, which may occur after orthodontic-orthognathic surgery treatment, may not be related to skeletal relapse after removal of the orthodontic appliances.